Innovation in Pedagogical Strategies through Artificial Intelligence: A Systematic Review - Moreno-Guaicha, Jefferson Alexander (2025)
The present study aims to identify AI tools applied in pedagogical strategies at different educational levels and analyze their outcomes. The methodology employed was a systematic review based on PRISMA guidelines. Starting with 683 studies identified in Scopus and Dimensions, 30 were selected after applying inclusion and exclusion criteria. The results were organized into five categories: improvement of learning and motivation (33,3%), which involves the use of tools such as adaptive systems and ChatGPT to personalize content and support individualized learning; intelligent tutoring (20%), focused on automated guidance; behavior analysis and feedback (20%), aimed at monitoring progress and continuous assessment; generation of educational resources (13,3%), centered on the automated creation of teaching materials; and integration into learning management platforms (13,3%), oriented toward the administration and access of educational content. The contribution of this study lies in systematizing and classifying AI applications in education, demonstrating their effectiveness in enhancing teaching quality and refining educational content. It concludes that, to maximize impact, a balanced approach is necessary—one that incorporates technical elements alongside essential pedagogical principles such as creativity, empathy, and critical thinking.